Women’s Employment and Entrepreneurship Programs Offered by NGOs in Egypt - Abdeen, Amany Ali, Ms. (AUC Knowledge Fountain, 2021)
Many non-governmental organizations (NGOs) in Egypt offer women employment and entrepreneurship programs and services. These interventions are envisioned to play a significant role in helping women become economically independent and overcome some of the constraints they face. These revolve around women’s limited access to strategic resources such as access to finance, skills and innovation assets. This study highlights the kinds of interventions offered by NGOs to support women beneficiaries by providing them with trainings, funding opportunities and couching services along with exploring the challenges these NGOs address. Moreover, both NGOs and women should be aware of the institutional laws and regulations in the business environment to connect these women with the market and make use of information and communications technology (ICT) and the facilities in the infrastructure. Qualitative in-depth interviews with NGOs’ CEOs, managing directors, project managers and staff members were used. The Covid-19 crisis occurred during the data collection which intensified the challenges addressed. The analysis of the study follows the conceptual framework of women empowerment and entrepreneurship including access, opportunities and awareness domains along with the six pillars identified by OECD that highly affect SMEs and entrepreneurs’ performance such as institutional and regulatory framework, market conditions, infrastructure, finance, skills, and innovation assets. The findings of this research show that there are various NGOs services offered for women beneficiaries to help them participate in the labor market. However, these interventions are not electronically recorded for regulatory authorities to track the available projects or the women benefiting from them. The study recommends compiling all initiatives in one database to effectively monitor the services offered to measure its impact on women economic empowerment and to enable more collaboration opportunities between different NGOs and the private and public sectors.